Phytosociological study in Pulo Felix, Taklong Island National Marine Reserve (TINMR), Nueva Valencia, Guimaras, Philippines. - Salmeron, Ramon Kit (2017.)
Small islands are unique ecosystems because of their high endemism attributed to their unique characteristics as influenced by geographic isolation, size, origin, elevation and geology. However, because of their small size, they are also highly vulnerable to many disturbances brought about by natural and anthropogenic factors such as coastal erosion, typhoons, climate change, tourism, invasive species, and many others. Consequently, many of these island floras are at risk of going instinct. In the Philippines, very few studies have been done to record the species found on many small islands. Therefore, this phytosociological study was done in Pulo Felix, TINMR, Nueva Valencia, Guimaras from December 2016 to April 2017 to describe, identify and classify the flora found on the island. Additionally, this study aimed to describe the community structure in terms of species composition, stand height, stand basal area, importance value and species diversity and evenness. Seven plots were randomly stationed at different locations on the island. In general, the floral composition include the mangroves and beach flora. A total of 60 species from 36 families were recorded, and an additional of four un-identified species; Family Fabaceae was the most represented family. In general, Pulo Felix had a fairly regenerative forest community based seedling density at 4,042.86 n ha-1 (42%), sapling density of 1,757.14 n ha-1 (18.2%) and tree density of 3,828.57 n ha-1 (39.8%). The most common and dominant species was Streblus asper with an importance value of 60.40. The total sample area was 700m2 wherein the total stand basal cover was 35.51 m2 ha-1. There was a low species diversity on the island based on the Shannon-Weiner diversity index, H?=1.11 and Simpson?s Eveness index, J?= 0.83. The presence of an invasive species, Leucaena leucocephala, was recorded that could possibly alter the overall floral composition of the native community. These findings will serve as benchmark information for future studies. It can also aid in the monitoring and management of the flora of the island.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the philippines, Miagao, Iloilo. 2017.
Keywords: Pulo Felix, Taklong Island -- Guimaras; Pulo Felix -- Physiological Study